Análisis agrosocioeconómico y ambiental, en la instalación, operación y ejecución de un biodigestor utilizando material orgánico (Estiércol de cerdo), para la generación y uso de biogas de los pobladores del sitio Garzas Chicas del cantón Mocache, provincia de Los Ríos. - Caicedo Gutiérrez, Mayra Alexandra (2014)
The research project "agrosocioeconomic AND ENVIRONMENTAL ANALYSIS IN THE INSTALLATION, OPERATION AND IMPLEMENTATION OF AN ORGANIC MATERIAL USING BIODIGESTOR (PIG MANURE) FOR THE GENERATION AND USE OF BIOGAS FROM PEOPLE SITE GARZAS CHICAS Mocache CANTON THE PROVINCE RIVERS” born product of fuel needs in this sector, which were analyzed through an agro-socio-economic survey to 32 families Campus”. One activity that prevails in the area is agriculture, becoming the Fort of the family economy; but their quality of life is affected as it encourages them and is difficult for them to obtain of domestic gas, since your transportation is more expensive than the same fuel; for this reason is proposed the installation of a bio-digester, which produces Biogas as there are primary inputs which are pig manure, physical space and the human resource, causing no affectation to the economy of 32 families..................................................................